KEBIJAKAN KEPALA SEKOLAH DALAM MENANGGULANGI KRISIS MORAL SISWA DI SD SITI AMELIA TEMBUNG KECAMATAN PERCUT SEI TUAN - Rini Andriani; Khairuddin Lubis; Armanila (STKIP Subang, 2025)
ABSTRACT This study aims to describe the principal’s policies in addressing students’ moral crisis at SD Siti Amelia. The moral issues observed include indiscipline, lack of respect toward teachers, and aggressive behavior such as bullying. This research employs a qualitative approach using observation, interviews, and documentation as data collection techniques.The findings show that the principal implements several strategic policies to address students' moral issues, including: (1) the application of educative consequences for students involved in moral violations, such as reading selected surahs from Juz 30, writing apology statements, and even parental summons; (2) collaboration with guidance counselors, homeroom teachers, and Islamic education teachers in character development through regular meetings and integrated moral guidance; and (3) requiring students to participate in Madrasah Diniyah Takmiliyah Awaliyah (MDA) as a form of strengthening Islamic religious education beyond school hours. Moreover, the principal uses Islamic extracurricular activities such as Qur’an memorization (tahfiz), Qur’anic recitation (tilawah), and Islamic music (nasyid) as a medium for fostering moral and religious character. The study concludes that the principal's policies play a significant role in building a religious, disciplined, and morally sound school environment, and are effective in addressing students’ moral crises. These policies align with the principal’s role as a moral and spiritual leader in Islamic education settings.